Engineering a riboswitch-based genetic platform for the self-directed evolution of acid-tolerant phenotypes - Hoang Long Pham (Nature Portfolio, 2017)
Cells are exposed to shifts in environmental pH, which direct their metabolism and behavior. Here the authors design pH-sensing riboswitches to create a gene expression program, digitalize the system to respond to a narrow pH range and apply it to evolve host cells with improved tolerance to a variety of organic acids.